PENGARUH PERILAKU WAJIB PAJAK MENGENAI TINGKAT PEMAHAMAN WAJIB PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DALAM MEMENUHI KEWAJIBAN PERPAJAKANNYA - Dahruji Inar (BALANCE: Economic, Business, Management and Accounting Journal, 2011)
This study is associative, this study entitled "The Effect of Tax Behaviour Understanding Concerning Rate Taxpayer and Taxpayer Awareness Against the Taxpayer Compliance Level Compliance tax obligations," Empirical studies on individual taxpayers in Bangkalan. It aims to study to determine the effect of two or more variables. This study proves the hypothesis that the taxpayer awareness and understanding of the taxpayer having effect on individual tax compliance. Based on the research that has been conducted in conjunction with data analysis and testing, it was found that the taxpayer awareness partially affect the compliance of the taxpayer. So is understanding the partially taxpayer also affect tax compliance. In addition, jointly or taxpayer awareness and understanding taxpayers also have an influence on tax compliance. Keywords: awareness of the taxpayer, the taxpayer understanding, compliance of the tax payer.